Accident with biological material in the surgical center: integrative literature review (Research, Society and Development, 2022)
Accidents with biological materials cause great concern in the scientific community and have aroused the interest of researchers, especially because of their harmfulness to the health of workers. Objective: to analyze the scientific evidences on exposure to biological material involving the health team in the surgical center. Methodology: this is an integrative literature review with searches in electronic databases such as PubMed, Embase, CINAHL, Scopus, Web of Science and Biblioteca Virtual em Saúde. Results: in the data collection 824 articles were identified, eliminating 179 duplicates. After reading the titles and abstracts of the 641 remaining articles, a total of 16 articles were selected, which met the criteria established for this integrative review on exposure to biological material. Of these, only four studies directly addressed exposure in the operating room. Conclusion: It is evident that accidents with exposure to biological material occur frequently in the surgical center unit; however, it was observed that few studies directly address exposure in this service.